Students' Views in Gamifying English Assessments for 11th Graders: Quizizz's Fun Twist at SMAN 3 Semarang - Rahayu, Dimitria; Chamami , M Rikza; Izza, Awwalia Fitrotin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
In the modern digital education landscape, traditional English language assessments, especially in the 11th grade, fail to engage students. This research aims to explore the perceptions of 11th-grade students at SMAN 3 Semarang regarding the gamification of English assessments through Quizizz, with a focus on its effectiveness in motivating students, alleviating anxiety, and improving learning outcomes. The research performed a qualitative investigation by conducting semi-structured interviews with six purposely selected students from the 11th grade who had experienced English assessments using Quizizz. Transcribed responses were analyzed thematically for patterns in learning, engagement, challenges, and preferences. The research discovered that through elements of gamification, such as instant feedback and points, Quizizz enhances the engagement of students by motivating them and making the assessments significantly more enjoyable than traditional tests. Quizizz also quickly reinforces vocabulary and grammar, though it can manifest some challenges, such as technical difficulties, anxiety over competition, and a limited ability to assess more advanced skills. The present educational game Quizizz serves as a motivated formative assessment tool, though a blended approach, integrating traditional assessments for summative evaluations, is necessary for equity and validity. The research underscores the need for pedagogical modifications to improve the use of gamification in English assessments.